2009
DOI: 10.1590/s0036-36342009000700004
|View full text |Cite
|
Sign up to set email alerts
|

The importance and relevance of peak bone mass in the prevalence of osteoporosis

Abstract: Peak bone mass and osteoporosis risk Artículo de revisión

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
150
1
17

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(171 citation statements)
references
References 71 publications
3
150
1
17
Order By: Relevance
“…Furthermore, this phenotype may be stage specific, as males tend to achieve peak bone mass later than females (Rizzoli et al 2001, Bonjour et al 2009, Stagi et al 2013; we cannot discard this augmented bone mass as it might occur at another time point. Further studies are warranted to determine how the absence of SR-BI alters the functions of adipocytes in female mice only and whether injection of leptin to male Scarb1-null mice mimics the bone phenotype of female Scarb1-null mice.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, this phenotype may be stage specific, as males tend to achieve peak bone mass later than females (Rizzoli et al 2001, Bonjour et al 2009, Stagi et al 2013; we cannot discard this augmented bone mass as it might occur at another time point. Further studies are warranted to determine how the absence of SR-BI alters the functions of adipocytes in female mice only and whether injection of leptin to male Scarb1-null mice mimics the bone phenotype of female Scarb1-null mice.…”
Section: Discussionmentioning
confidence: 86%
“…It is a well-known fact that men tend to achieve higher peak bone mass than do women, presumably due to the longer period of bone mass gain in the former (Rizzoli et al 2001). Bone accrual is also site specific within the same skeleton, with preferential bone mineral accumulation in the lumbar vertebrae and femoral neck (Rizzoli et al 2001, Bonjour et al 2009); these also happen to be common sites for osteoporotic fractures and show the greatest gender-related dimorphism (Raisz 2005, Bonjour et al 2009). Several determinants of peak bone mass are common to that of osteoporosis; factors that compromise bone mass are attributed to race, smoking, inactive lifestyle, malnutrition, and underlying metabolic disorders such as diabetes and atherosclerosis are often associated with lower bone mass (Leidig-Bruckner & Ziegler 2001, Sweet et al 2009, Stojanovic et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…After the end of the growth period, in early adulthood, the bone is still remodeled by resorption performed by osteoclasts and apposition by osteoblasts [24]. Acquisition of bone mineral continues throughout childhood and adolescence, reaching a lifetime maximum ('peak bone mass') in early adulthood [25]. In old adulthood (>65 years), decrease in bone mass density is usual, due to an unbalanced remodeling process [26].…”
Section: Discussionmentioning
confidence: 99%
“…The condition is a major public health problem in the Western countries and is projected to have a similar impact in the Middle East [1,2]. It has been suggested that peak Bone Mineral Density (BMD), which can be defined as the amount of bony tissue present at the end of the skeletal maturation, is a major determinant of osteoporotic fractures later on in life [3][4][5][6]. The probable importance of achieved peak bone mass for late life bone strength was first suggested by the cross-sectional observation of Newton-John and Morgan that the dispersion of bone mass values was not widened by age [7].…”
Section: Introductionmentioning
confidence: 99%